2017
DOI: 10.1002/chem.201700659
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Lewis Acidity by a Transannular pπ–σ* Interaction between Boron and Silicon/Germanium Atoms Supported by a Cage‐Shaped Framework

Abstract: Cage-shaped borates tethered by heavier Group 14 elements (Si or Ge) were synthesized. These possess an intramolecularly transannular p -σ* interaction between the boron center and the tethered Si/Ge atom, which allows the precise tuning of their Lewis acidity. The Lewis acidity was investigated by the ligand-exchange reaction rate and IR measurements with the help of theoretical calculation. The synthesized borates exhibited catalytic activity. This study demonstrated the effectiveness of the direct orbital p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Knowing that several free or coordinated non‐planar boron Lewis acids are known, such as borabenzobarrelene 7 (Scheme ), 1‐bora adamantane 8 , and 9 , we have been stimulated to generate the boratriptycene Lewis acid 6 and to design Lewis acid/base bifunctional molecules such as 10 with a B atom and a P atom at each edge of the triptycene framework (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing that several free or coordinated non‐planar boron Lewis acids are known, such as borabenzobarrelene 7 (Scheme ), 1‐bora adamantane 8 , and 9 , we have been stimulated to generate the boratriptycene Lewis acid 6 and to design Lewis acid/base bifunctional molecules such as 10 with a B atom and a P atom at each edge of the triptycene framework (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…The ν C=O stretching frequency in 25 is even lower than in AlCl 3 ⋅EtOAc (1624 cm −1 ) . This strong Lewis acidity enhancement is the result of the electron‐withdrawing effect of the phosphonium linker and to a transannular overlap between the vacant p‐orbital of boron and σ* orbital of the phosphonium in the triptycene scaffold.…”
Section: Methodsmentioning
confidence: 99%
“…With the development of photoactivated Lewis acids in mind, we focused on a cage-shaped triphenolic ligand, which has established its effectiveness in controlling the Lewis acidity of a boron [38,39] or an aluminum atom. [40] The Lewis acidity of the cage-shaped borate 1B can be tailored by changing the tethered atom and its substituent (XÀ Y), [41] the substituents (R), [42][43][44] and/or the π-conjugated system (π) (Figure 1B). [45,46] We previously reported that benzofuran-based cage-shaped borate 2B exhibited enhanced catalytic activity under black light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The high accessibility of the tripodal ligand has ensured that chemical modifications of cage‐shaped Lewis acids, which lead to fine control of the Lewis acidity, [55, 56] enables a variety of catalytic activities [57–59] . The feasibility of chemical modifications of complex 1 b B prompted us to investigate the electronic and/or geometric effects of a π‐pocket on molecular recognition.…”
Section: Introductionmentioning
confidence: 99%